Maqasid Shariah (Pentagon-Shaped Ethical Measurement) Establish Organizational Performance: a conceptual framework - Hadi, Syamsul; Iswantoro, Ibnu Yanuar; Purnasari, Eni; Wahyuningtiyas, Nabila; Andleeb, Naima (Journal of Islamic Economics and Social Science (JIESS), 2022)
Purpose –This paper aims to review the impact of Maqasid Shariah on Organizational performance from several organizational levels literature. Design/methodology/approach –This paper focused on exploring the literature published in various popular databases. Based on the conceptual analysis, a set of possible frameworks was stated for future research. Findings –The research has evolved with a few possible frameworks to model the assertions by investigating and corroborating them with quantitative studies to be empirically tested. Originality/value – The originality lies in presenting an analysis of the maqasid shariah conceptual framework using al-Ghazali on organizational performance (non-financial treatment). thereby adding new insights to the maqasid shariah literature.